Synthesis, Application and Evaluation of Bismuth Sulfide (Bi2s3) Metal Nanoparticles as Nanocarriers for Poorly Soluble Class II Drug Clarithromycin - Mustafa R. Abdulbaqi (Journal of Global Pharma Technology, 2016)
Objective: The aim of this study was to evaluate the effect of bismuth sulfide Bi2S3 metalnanoparticles as carries on the pharmaceutical properties and biologic activity of Biopharmaceutical Classification System (BCS) class II drug clarithromycin (CLA). Methods: Bismuth sulfide (Bi2S3) nanoparticles synthesized by chemical co-precipitation technique, during which CLA loaded (incorporation method). Characterizations techniques including atomic force microscopy (AFM), X-ray diffraction (XRD) and fourier transform infra-red spectroscopy (FTIR) were used for particle size and particle size distribution, crystal lattice and compatibility, respectively. USP puddle apparatus type II (in phosphate buffer solution pH 7.4) was used for in-vitro release study. Disc diffusion method was the technique used to test the antibacterial activity of blank Bi2S3 nanoparticles; free CLA (as control) and CLA loaded metal nanoparticles. Results: CLA was loaded successfully with synthesized Bi2S3 nanoparticles by physical interaction without any chemical modification, as approved by FTIR. Particle size of CLA was reduced from 116.17 to 95.5 nm after loading process with uniform particle size distribution (as measured by AFM). In vitro release study demonstrated complete release of CLA from Bi2S3 nanoparticles after 120 min, indicating significant*increase in the solubility and dissolution profile of CLA after loading process. XRD spectrum showed lattice transition from crystalline into amorphous structure. Susceptibility test displayed significant*potentiation of antibacterial activity at all tested concentrations against gram +ve bacteria Staphylococcus aureus and Bacillus subtilis after loading of CLA with Bi2S3 nanoparticles, while gram –ve bacteria E. coli showed no response for CLA before and after loading process. Bi2S3 nanoparticles showed no antibacterial activity against all tested bacterial cultures. Conclusion: The use of synthesized metal Bi2S3 nanoparticles, as nanocarriers, was applied successfully as an attractive delivery system for the improvement in the solubility, dissolution profile and biologic activity of BCS class II drug CLA.Keywords: Class II drug; Clarithromycin (CLA); Bismuth sulfide (Bi2S3)nanoparticles.